Malawi Health Sector Strategic Plan - Malawi Government: Ministry of Health (Ministry of Health, 2021)
It is the desire of the Government of Malawi to have the highest possible level of health and quality of life for its citizens. Improving the health of the nation through the combined efforts of individuals, communities, organizations, our co-operating partners and the Government is therefore one of the key priorities. The formulation and launch of the national Health Sector Strategic Plan (2011-2016) build on the sustained gains made under the Program of Work (2004-2010). Considerable improvements in the delivery of an Essential Health Package (EHP) have been registered in reducing infant and child mortality rates, pneumonia case fatality and maternal mortality, and in maintaining high immunization coverage, among other areas. Unlike the Program of Work, this Plan has taken further measures to address the burden of disease by delivering an expanded EHP through public health interventions including but not limited to health promotion, disease prevention and increasing community participation. The Plan provides the framework that will guide the efforts of the Ministry of Health and all stakeholders over the next 5 years in contributing to the attainment of the Malawi Growth and Development Strategy (MGDS-II) and the Millennium Development Goals (MDGs). In cognizance of this, therefore, the emphasis will be on increasing coverage of high quality EHP services; strengthening performance of the health system to support delivery of EHP services; reducing risk factors to health and improving equity and efficiency in the delivery of free, quality EHP services in Malawi, thereby contributing to poverty reduction and the socio economic development of the nation. The successful implementation of this plan will depend on the continued dedication of staff in the Ministry of Health and those of its partner organizations. We welcome the support of our co-operating partners, we gratefully acknowledge their contribution towards the development of the HSSP and look forward to their continued support in its implementation. As a policy document that we have jointly formulated, it is my sincere hope that it will henceforth become the single most important point of reference for design of service delivery programmes, resource mobilization and health financing framework, as it embodies our dream for a better health care delivery system for all the people of Malawi.